Young people from Bosnia talk about war - Fireside, Harvey; Fireside, Bryna J. (Springfield, NJ : Enslow Publishers, 1996)
Gives a brief description of the conflict in Bosnia, including several personal stories of tragedy told by the young people who lived through them.
Includes bibliographical references (p. 99-101) and index.
Keywords: Yugoslav War, 1991-1995 -- Personal narratives, Bosnian -- Juvenile literature; Yugoslav War, 1991-1995 -- Children -- Juvenile literature; Yugoslav War, 1991-1995 -- Bosnia and Herzegovina -- Juvenile literature; Children -- Bosnia and Hercegovina -- Biography -- Juvenile literature; Yugoslav War, 1991-1995.; Bosnia and Herzegovina -- History -- 1992- -- Juvenile literature; Bosnia and Herzegovina -- History